2011
DOI: 10.1152/ajplung.00094.2011
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of alveolar epithelial sodium channel activity with decreased cystic fibrosis transmembrane conductance regulator expression in mouse lung

Abstract: Lazrak A, Jurkuvenaite A, Chen L, Keeling KM, Collawn JF, Bedwell DM, Matalon S. Enhancement of alveolar epithelial sodium channel activity with decreased cystic fibrosis transmembrane conductance regulator expression in mouse lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 66 publications
5
46
0
Order By: Relevance
“…Similar recordings were obtained from dozens of ATII cells and nine ATI cells, both in slices from five mice, with identical results. These findings are in agreement with our recently published results (18). Alveolar macrophages (identified by their size, shape, and morphology) did not show amiloride sensitive-channel activity (data not shown), in agreement with our previous report (24).…”
Section: Single-channel Recordings From Murine Alveolar Cells In Situsupporting
confidence: 94%
See 1 more Smart Citation
“…Similar recordings were obtained from dozens of ATII cells and nine ATI cells, both in slices from five mice, with identical results. These findings are in agreement with our recently published results (18). Alveolar macrophages (identified by their size, shape, and morphology) did not show amiloride sensitive-channel activity (data not shown), in agreement with our previous report (24).…”
Section: Single-channel Recordings From Murine Alveolar Cells In Situsupporting
confidence: 94%
“…Lung slices were prepared as previously described (18). The right lower lobes were dissected (without being filled with agar solution) and stored in Krebs solution at 4 8 C. They were then attached to the jig of an OTS 5000 slicer (FHC, Inc., Bowdoinham, ME), using cyanoacrylate adhesive gel, and sectioned longitudinally with a zirconium blade into 200-to 250-mmthick slices at 4 8 C. The slices were then transferred to a six-well plate containing approximately 2 ml Dulbecco's Modified Eagle's Medium without serum, supplemented with penicillin-streptomycin, and allowed to recover at 37 8 C in a humidified environment of 95% air/5% CO 2 for 2 to 3 hours.…”
Section: Preparation Of Lung Slicesmentioning
confidence: 99%
“…An association between CFTR and ENaC was first reported by Stutts et al (367), who showed that amiloride-sensitive Na ϩ transport was reduced in cells expressing both channels, whereas expression of ENaC alone was associated with large inward currents. These data suggested that wild-type CFTR exerted an inhibitory effect on ENaC to reduce ENaC P o , a finding that has been replicated by several groups (201,241,251,368). The mechanism underlying this functional interaction is, however, controversial, having been variously attributed to changes in intracellular chloride affecting ENaC activity (25, 54, 230), through changes in electrical driving force (73,181,202), to technical issues surrounding efficiency of voltage clamping (282).…”
Section: Conditions Associated With Enac Hyperactivity: Hypertension mentioning
confidence: 85%
“…Several excellent recent publications focused on the crucial role of CFTR in the regulation of alveolar fluid balance and its interplay with ENaC and other ion channels and transporters in vitro and in vivo (3,4,6,10,(12)(13)(14). In addition to being a key regulator of ELF, there is growing evidence that CFTR plays a role in modifying immune response (7).…”
mentioning
confidence: 99%
“…Also, given that CFTR has been implicated in the regulation of ENaC and vice versa (3,12,14,17,22,25) and M2 downregulates both channels [by apparently different mechanisms (11,15)], it will be interesting to see whether M2 also alters the interplay of the two transporters in the distal lung epithelium. Moreover, since CFTR has been shown to be differentially expressed in distinct cells types and locations of the airway (3) it will be crucial to test whether these in vitro findings will hold up in vivo systems, to gauge the translational importance of the M2-CFTR interaction.…”
mentioning
confidence: 99%